2022
DOI: 10.1111/imm.13585
|View full text |Cite
|
Sign up to set email alerts
|

Alternative pathway dysregulation in tissues drives sustained complement activation and predicts outcome across the disease course in COVID‐19

Abstract: Complement, a critical defence against pathogens, has been implicated as a driver of pathology in COVID‐19. Complement activation products are detected in plasma and tissues and complement blockade considered for therapy. To delineate roles of complement in immunopathogenesis, we undertook the largest comprehensive study of complement in an COVID‐19 to date, a comprehensive profiling of 16 complement biomarkers, including key components, regulators and activation products, in 966 plasma samples from 682 hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 54 publications
3
26
0
Order By: Relevance
“…10 Progressive changes in the concentrations of some complement biomarkers have also been reported in the context of severe disease. 10,[14][15][16][17]19 In mechanistic terms, complement activation under these circumstances has been variously attributed to direct virus-mediated triggering of the classical, lectin, and/or alternative pathways, activation of the classical pathway via antiviral antibodies, and/or indirect activation via contact with infected cells and/or damaged tissue. [20][21][22][23][24] These observations have been used to rationalize interventions with complement blocking drugs to mitigate the hyperinflammatory state that characterizes severe COVID-19.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…10 Progressive changes in the concentrations of some complement biomarkers have also been reported in the context of severe disease. 10,[14][15][16][17]19 In mechanistic terms, complement activation under these circumstances has been variously attributed to direct virus-mediated triggering of the classical, lectin, and/or alternative pathways, activation of the classical pathway via antiviral antibodies, and/or indirect activation via contact with infected cells and/or damaged tissue. [20][21][22][23][24] These observations have been used to rationalize interventions with complement blocking drugs to mitigate the hyperinflammatory state that characterizes severe COVID-19.…”
Section: Discussionmentioning
confidence: 98%
“…Dysregulation of the complement cascade has been implicated as a driver of inflammation in many diseases, including acute COVID-19. [9][10][11][12] Indeed, the complement system is markedly dysregulated in severe acute COVID-19, and biomarkers spanning all activation pathways predict disease outcome. 10,[13][14][15][16][17] On the basis of these observations, we hypothesized that complement dysregulation could play a key role in the pathogenesis of long COVID.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of several complement factors (C3 and C5) are observed in the plasma of COVID-19 patients and these factors are correlated to disease severity ( 223 , 224 ). In a non-randomized clinical trial, eculizumab (a C5 inhibitor) significantly improved 15-day survival and oxygenation in severe COVID-19 patients ( 225 ).…”
Section: Treatment Strategymentioning
confidence: 99%
“…All three complement arms were shown to be activated in COVID-19 (17)(18)(19)(20)(21)(22)(23)(24); however, their relative contributions remain ill-defined. Whereas complement was initially described as a liver-derived cascade, studies have demonstrated unexpected celland tissue-specific production and functions for the complement system (8,(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%